2018
DOI: 10.3390/socsci7110223
|View full text |Cite
|
Sign up to set email alerts
|

When Academic Technology Fails: Effects of Students’ Attributions for Computing Difficulties on Emotions and Achievement

Abstract: As education experiences are increasingly mediated by technology, the present research explored how causal attributions for academic computing difficulties impacted emotions and achievement in two studies conducted with post-secondary students in North America and Germany. Study 1 (N = 1063) found ability attributions for computer problems to be emotionally maladaptive (more guilt, helplessness, anger, shame, regret, anxiety, and boredom), with strategy attributions being more emotionally adaptive (more hope, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Early studies showed that 25%–50% of adults, including first‐year undergraduate students, had anxiety related to using computers and technology (Rosen & Maguire, 1990; Weinberg & Fuerst, 1984). While this percentage is expected to decrease with time as technology becomes more prevalent in education, there is still prevalent anxiety in using computer and technology as educational resources (Maymon, Hall, & Goetz, 2018). Therefore, teaching in an online environment may amplify some of these anxious feelings in students.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed that 25%–50% of adults, including first‐year undergraduate students, had anxiety related to using computers and technology (Rosen & Maguire, 1990; Weinberg & Fuerst, 1984). While this percentage is expected to decrease with time as technology becomes more prevalent in education, there is still prevalent anxiety in using computer and technology as educational resources (Maymon, Hall, & Goetz, 2018). Therefore, teaching in an online environment may amplify some of these anxious feelings in students.…”
Section: Introductionmentioning
confidence: 99%